Study on the Odd-Even Periodic Table of Chemical Elements - Wu, Zhifu (Technium BioChemMed, 2020)
Odd-Even periodic table of chemical elements designed by the authors settles the position of Hydrogen and Helium. Additionally, it yields no exceptional arrangements for neither the Lanthanides, Actinide and super Actinides nor the six empty spots and the controversy on the positions of hydrogen and helium have been settled. It plays an important role in comparing the stability of nucleons and predicting the ordinal of the terminal element.